Magnetic Resonance-Guided Focused Ultrasound Surgery for Obsessive-Compulsive Disorders: Potential for use as a Novel Ablative Surgical Technique - Chang, Kyung Won; Jung, Hyun Ho; Chang, Jin Woo (Frontiers in Psychiatry, 2021)
Surgical treatment for psychiatric disorders, such as obsessive-compulsive disorder (OCD) and depression, using ablative techniques, such as cingulotomy and capsulotomy, is considerably controversial for a number of scientific, social, and ethical reasons. Recently, with the elucidation of anatomical and neurochemical substrates of brain function in healthy controls and patients with such disorders using various functional neuroimaging techniques, these criticisms are becoming less valid. Furthermore, by using new techniques, such as deep brain stimulation (DBS), and identifying more precise targets, beneficial effects and the lack of serious complications have been demonstrated in patients with psychiatric disorders. However, DBS also has many disadvantages. Currently, magnetic resonance-guided focused ultrasound surgery (MRgFUS) is used as a minimal-invasive surgical method for generating precisely placed focal thermal lesions in the brain. Here, we review surgical techniques and their potential complications, along with anterior limb of the internal capsule (ALIC) capsulotomy by radiofrequency lesioning and gamma knife radiosurgery, for the treatment of OCD and depression. We also discuss the limitations and technical issues related to ALIC capsulotomy with MRgFUS for medically refractory OCD and depression. Through this review we hope MRgFUS could be considered as a new treatment choice for refractory OCD.